2011
DOI: 10.1111/j.1654-109x.2010.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of Campylopus introflexus in drift sands depends on nitrogen deposition and soil organic matter

Abstract: Question: Does the neophyte moss Campylopus introflexus invade more often in drift sand pioneer vegetations under high nitrogen (N) deposition? Location: Fourteen inland dune reserves in The Netherlands over a gradient of atmospheric N deposition. Methods: A transect study, dispersal experiment and culture experiment were carried out. In the transect study, the establishment of C. introflexus and lichens was measured in pure mats of Polytrichum piliferum, an early succession stage. The overall presence of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…We selected environmental data regarding eco-physiological constraints of the target taxa according to recent literature on habitat preferences (Frahm & Stech, 2006;Klinck, 2010;Spagnuolo et al, 2014;Sparrius & Kooijman, 2011;Sparrius, Sevink, & Kooijman, 2012). The selected 10 environmental variables were obtained from WorldClim (www.worldclim.org) and are of high spatial and temporal resolution.…”
Section: Ecological Niche Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected environmental data regarding eco-physiological constraints of the target taxa according to recent literature on habitat preferences (Frahm & Stech, 2006;Klinck, 2010;Spagnuolo et al, 2014;Sparrius & Kooijman, 2011;Sparrius, Sevink, & Kooijman, 2012). The selected 10 environmental variables were obtained from WorldClim (www.worldclim.org) and are of high spatial and temporal resolution.…”
Section: Ecological Niche Comparisonsmentioning
confidence: 99%
“…Besides Europe, C. introflexus was introduced in North America (Carter, 2014). Its negative impact on the biodiversity of natural habitats such as coastal and inland dunes, especially lichen-rich gray dunes (Essl et al, 2014;Klinck, 2010;Sparrius & Kooijman, 2011), should have brought attention to its troublesome delimitation from closely related species, especially Campylopus pilifer Brid. (Frahm, 1974;Frahm & Stech, 2006;Gradstein & Sipman, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen deposition was found to cause faster growth and early settlement of thick mats of the invasive bryophyte Campylopus introflexus , leaving less space for lichen vegetation (Sparrius & Kooijman ); that study includes several sites for which results are reported here. We indeed observed that the relative cover of the Campylopus vegetation class is much higher in regions with high N deposition in both active and more stabilized drift sand.…”
Section: Discussionmentioning
confidence: 99%
“…In both sites, plots were selected in three different vegetation types, which can be compared with those of Hasse (): (1) Polytrichum piliferum mats that had recently developed on bare sand with a minimum of 90% moss cover and a maximum of 10% grasses (mostly tussocks of Corynephorus canescens ) on a 2–3‐cm thick A h horizon; (2) Campylopus introflexus ‐dominated vegetation with over 90% moss cover and sparse presence of grasses and lichens on a 3–4‐cm thick A h horizon, which usually develops on older Polytrichum piliferum mats and may be interpreted as an alternative stable state for young lichen vegetation under high N deposition or after disturbance (Sparrius & Kooijman ); and (3) species‐rich Cladonia ‐dominated vegetation (mainly Cladonia portentosa, C. cervicornis, C. gracilis and C. furcata ) with over 30% lichen cover on a 6–7‐cm thick A h horizon, which may develop from Campylopus mats and vegetation with small lichen species. This last vegetation type also develops on Polytrichum piliferum mats, but is generally older than the Campylopus type, which is reflected in the thicker A h horizon.…”
Section: Methodsmentioning
confidence: 99%
“…). In the 1960s, introduction of the invasive bryophyte Campylopus introflexus (Hassel & Söderström ) added a new threat to the lichen‐dominated grassland communities of the inland dunes, as this species partially replaced vegetation dominated by smaller lichens (Ketner‐Oostra & Sýkora ), especially in areas with high N deposition (Sparrius & Kooijman ). Further successional stages, i.e.…”
Section: Introductionmentioning
confidence: 99%